OVERVIEW OF THE APPLICATION OF THE CONCEPT OF GREEN MARKETING IN ENVIRONMENT CONSERVATION - Kadar Nurjaman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The concept of a green marketing mix is similar to that of a standard marketing mix in that both aim to satisfy customer needs, wants, and preferences while also contributing to environmental protection and upkeep. The environmental consciousness of consumers gives chances for businesses to implement green marketing and enhance sales. Green marketing becomes an alternative technique that not only improves the company's image, but also adds value to the company's business; consumers even want green options and are willing to pay a premium for them. The marketing strategy comprises of the company's external and internal components, whereas the marketing mix strategy is the fundamental concept and generic function of marketing, comprising product, price, place, and promotion elements that influence the occurrence of sales. Developing the green marketing mix (green marketing mix) is detachable from the classic 4P concept (product, pricing, location, promotion), with the inclusion of a number of components intimately tied to the purpose of green marketing and other highly relevant factors. Implementing a green marketing strategy necessitates a fundamental, comprehensive, and integrated approach to all functional components of marketing, such as the marketing mix, product design, price, location, and promotion.